Pengabaian Nafkah Lahir Sebagai Alasan Perceraian Di Pengadilan Agama Pangkajene Klas 1B (Studi Kasus Tahun 2021) - Sakirah Sakirah (Al Fuadiy Jurnal Hukum Keluarga Islam, 2023)
The matter of maintenance as the reason for this divorce is because the husband is unable to provide a living or the husband is actually able to provide a living but does not want to provide a living even though his wife lives in poverty. Living is the obligation of a husband to give something to his wife, relatives and possessions as a basic need for them. The law of maintenance is obligatory which is the wife's right to her husband as a result of a valid marriage contract. If the husband does not address the problem of subsistence in the family, then what will arise is a problem that cannot be resolved, it will have an impact on household harmony, and even lead to divorce.